BTF3 promotes proliferation and glycolysis in hepatocellular carcinoma by regulating GLUT1 - Peng Wang; Jianmin Sun; Chengming Sun; Haoran Zhao; YuBao Zhang; Jing Chen (Cancer Biology & Therapy, 2023)
Hepatocellular carcinoma (HCC) is a grievous tumor with an increasing incidence worldwide. Basic transcription factor 3 (BTF3) is discovered to regulate the expression of glucose transporter 1 (GLUT1), which benefits glycolysis, a momentous signature of tumors, through transactivation of the forkhead box M1 (FOXM1) expression. BTF3 is highly expressed in HCC. However, whether BTF3 promotes GLUT1 expression through FOXM1 to modulate glycolysis in HCC remains unclear. The expression profile of BTF3 were determined by online database, reverse transcription-quantitative polymerase chain reaction (RT-qPCR) and western blot. The role and mechanism of BTF3 in the proliferation and glycolysis of HCC cells were examined by cell counting kit-8 (CCK-8), 5-ethynyl-2′-deoxyuridine (EdU) incorporation, XF96 Extracellular Flux analyzer, spectrophotometry and western blot analysis. In addition, the direct interaction between BTF3 and FOXM1 was verified by dual-luciferase reporter and co-immunoprecipitation assays. Moreover, the role of BTF3 was also explored in a xenografted mice model. The expression of BTF3 was increased in HCC cells and tumor tissues. Knockdown of BTF3 reduced the cell viability, Edu positive cells, extracellular acidification rate (ECAR), glucose consumption and lactate production in both Huh7 and HCCLM3 cells. The expressions of FOXM1 and GLUT1 were increased in HCC tissues, which were positively correlated with the BTF3 expression. Moreover, a direct interaction existed between BTF3 and FOXM1 in HCC cells. Downregulation of BTF3 decreased the relative protein levels of FOXM1 and GLUT1, which were rescued with overexpression of FOXM1 in both cells. More importantly, overexpression of FOXM1 restored the cell viability, ECAR, glucose consumption and lactate production in both Huh7 and HCCLM3 cells transfected with siBTF3#1. Furthermore, inhibition of BTF3 decreased tumor weight and volume, and the relative level of BTF3, FOXM1, GLUT1 and Ki-67 in tumor tissues from mice xenografted with Huh7 cells. BTF3 enhanced the cell proliferation and glycolysis through FOXM1/GLUT1 axis in HCC.